(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with the concept of almost nearly quasi (τ_1,τ_2)-continuous multifunctions. Moreover, several characterizations and some properties concerning almost nearly quasi (τ_1,τ_2)-continuous multifunctions are considered.